Sustainable radiation shielding: CeO2-doped polyhydroxyalkanoate (PHA) composites for gamma attenuation - Kok, Mediha; Tatar, Cengiz; Oner, Ecem Ozen; Pekdemir, M. Ersin; Tatar, Beyhan; Taze, Alev; Aydogdu, Yildirim (Taylor & Francis Ltd, 2025)
The development of advanced materials with enhanced functional properties remains a key focus in materials science. In this study, polymer composites comprising biodegradable polyhydroxyalkanoate (PHA) and cerium oxide (CeO2), a rare earth oxide, were fabricated and systematically characterized. The influence of varying CeO2 content (1-15 wt%) on the structural, thermal, and gamma radiation shielding properties of the composites was thoroughly investigated. Thermal analysis revealed that the incorporation of 15 wt% CeO2 increased the residual mass at 500 degrees C from 0% (pure PHA) to approximately 19%, indicating improved thermal stability without significantly altering the melting temperature (Tm approximate to 157 degrees C). X-ray diffraction (XRD) analysis showed increased crystallinity with higher CeO2 concentrations, accompanied by the appearance of additional diffraction peaks associated with CeO2. Furthermore, the linear attenuation coefficient (mu) at 0.662 MeV rose from 0.084 cm-1 (pure PHA) to 0.162 cm-1 (15 wt% CeO2), while the half-value layer (HVL) decreased from 8.25 to 4.28 cm, reflecting a substantial improvement in gamma radiation shielding capability. Overall, the PHA/CeO2 composites demonstrate strong potential as lightweight, environmentally friendly materials for radiation shielding applications.
Keywords: Polyhydroxyalkanoate (PHA); rare earth element; shape memory effect; radiation shielding; composite